EDUCATION LEVEL AND KNOWLEDGE LEVEL IN OPEN DEFECATION BEHAVIOR - Nugroho, Purwo Setiyo; Wiarisa, Hesty; Wulandari, Murni (Krafon Publishing, 2019)
Introduction: Open defecation behavior is a problem for developing countries including Indonesia. This can cause a dirty environment and a source of transmission of diseases such as diarrhea and other infectious diseases. So there needs to be research that analyzes the risk factors for these behaviors. This study aims to analyze the relationship of knowledge and education level to defecation behavior in all areas. Methods: A total of 110 family heads were examined and selected using the proportional random sampling technique. The statistical analysis used is Chi Square. Results: The results of the analysis found that there was a relationship between the level of education (p=0.041; OR=2.576; 95% CI=1.118-5,934) and knowledge (p=0.001 OR=4,000; 95% CI=1.794-8,920) towards open defecation behavior. There needs to be an effort from various parties to be able to increase knowledge through periodic education and the use of health promotion media that can be accessed anytime and anywhere.